Varnhagen in movement: a brief anthology of an existence - Temístocles Cezar; Eoin Paul O'Neill (Topoi)
The purpose of this article is to outline a life and work brief anthology of historian Francisco Adolfo de Varnhagen (1816-1878), who lived mainly out of Brazil. I try to relate part of his extensive work to a distant look, as an effect of his continuous movement in search of files and documents on Brazil's history and geography which were found abroad. In addition, i intend to emphasize the relevance of journeys and in locu wiews as cognitive resources for writing history in a context characterized by the emergence of history as a science and its claim for narrative objectivity and for historians impartiality.